2002
DOI: 10.1590/s0103-64402002000300010
|View full text |Cite
|
Sign up to set email alerts
|

Bonding brackets to porcelain: in vitro study

Abstract: The aim of this research was to verify, in vitro, the effect of various porcelain surface treatments on the shear strength of orthodontic brackets bonded to porcelain and the mode of fracture after debonding. Eighty-eight samples of metallic supported feldspathic porcelain were randomly divided into four groups according to their surface preparation as follows: the porcelain was maintained intact (GI), roughened with a diamond bur (GII), etched with 10% hydrofluoric acid (GIII), or sandblasted with aluminum ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
15

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 16 publications
(21 reference statements)
3
32
0
15
Order By: Relevance
“…Although clinicians should follow the manufacturers' recommendations for bonding procedures, a 60 s etching time for bonding to feldspathic ceramic might be recommended. However, care should be taken when selecting the etching time for each substrate, as previous studies have shown negative effects of over-etching ceramics, such as difficult penetration of the bonding agent into the irregularities and possible cohesive failure of the substrate (1)(2)(3)(4)19,20). On the other hand, although the light source presented …”
Section: Discussionmentioning
confidence: 99%
“…Although clinicians should follow the manufacturers' recommendations for bonding procedures, a 60 s etching time for bonding to feldspathic ceramic might be recommended. However, care should be taken when selecting the etching time for each substrate, as previous studies have shown negative effects of over-etching ceramics, such as difficult penetration of the bonding agent into the irregularities and possible cohesive failure of the substrate (1)(2)(3)(4)19,20). On the other hand, although the light source presented …”
Section: Discussionmentioning
confidence: 99%
“…The use of 50-μm aluminum oxide particle stream has been recommended for bracket recycling to increase retention by creating a roughened surface (18,19). In the present study, bracket blasting was done using the aluminum oxide particle size (90 μm) indicated in the instructions for use supplied by the manufacturer of the air-abrasion device.…”
Section: Discussionmentioning
confidence: 99%
“…Para se colar bráquetes ortodônticos em restaurações cerâmicas é necessário preparar a superfície, removendo ou não o glaze. Já foi demonstrado não haver diferença estatística entre estes dois métodos, sugerindo preservar a superfície glazeada para diminuir os prejuízos à superfície de porcelana que se deseja preservar [25,26]. Analisando a resistência ao cisalhamento neste estudo, onde o glazeamento da superfície foi preservado e obtido de formas diferentes, força de adesão menor foi encontrada quando usada resina fotopolimerizável em superfície auto-glazeada (10,38 ± 4,1 MPa), mas acima da média aceitável na literatura.…”
Section: Discussionunclassified